2012
DOI: 10.1378/chest.12-0148
|View full text |Cite
|
Sign up to set email alerts
|

Translational Educational Research

Abstract: Medical education research contributes to translational science (TS) when its outcomes not only impact educational settings, but also downstream results, including better patient-care practices and improved patient outcomes. Simulation-based medical education (SBME) has demonstrated its role in achieving such distal results. Effective TS also encompasses implementation science, the science of health-care delivery. Educational, clinical, quality, and safety goals can only be achieved by thematic, sustained, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(22 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Additional work includes longitudinal data collection of staff attitudes over longer time periods, comparison of different methods of training and curriculum design, as well as a higher level of evaluation in the definitions of translational educational research to include patient outcomes or direct indices of care safety and quality. 18 , 25 Finally, validation studies of our interprofessional curriculum across different clinical sites may expand the applicability of the training methodology used in our study to a wider spectrum of institutions and departments.…”
Section: Impactmentioning
confidence: 91%
“…Additional work includes longitudinal data collection of staff attitudes over longer time periods, comparison of different methods of training and curriculum design, as well as a higher level of evaluation in the definitions of translational educational research to include patient outcomes or direct indices of care safety and quality. 18 , 25 Finally, validation studies of our interprofessional curriculum across different clinical sites may expand the applicability of the training methodology used in our study to a wider spectrum of institutions and departments.…”
Section: Impactmentioning
confidence: 91%
“…Several studies have demonstrated the efficiency of simulation for knowledge acquisition and for technical (6)(7)(8) and non-technical (9,10) skills training in healthcare. Training healthcare professionals to manage rare or critical events in a standardized manner and without risk for the patient has become a major challenge (11) .…”
Section: Introductionmentioning
confidence: 99%
“…We believe that this is the way that we can address what have been called complex service interactions in the clinical arena where multi-person teams are interacting around real patients in dynamic and complex care settings that have constant change. 37 Goldhaber-Fiebert and colleagues recently summarized this implementation schema of any cognitive aid as: Create, Familiarize, Use, Integrate. 29 In addition, payors, professors, and private practitioners should now join forces to ensure that a culture obtains where these tools, having been created, are ones that all members of our care teams become familiar with, use, and integrate into healthcare systems so that we are better prepared when the rare event occurs.…”
Section: Discussionmentioning
confidence: 99%